2020
DOI: 10.1002/aoc.5467
|View full text |Cite
|
Sign up to set email alerts
|

Novel NiFe/Si/Au magnetic nanocatalyst: Biogenic synthesis, efficient and reusable catalyst with enhanced visible light photocatalytic degradation and antibacterial activity

Abstract: The aim of this paper is to biosynthesize NiFe2O4/SiO2/Au (NiFe/Si/Au) magnetic nanocatalyst using the sonochemical method. This is the first study to synthesize this compound using this method. To obtain optimum morphology and size of products, the synthesis was performed in the presence of polyvinylpyrrolidone, maltose, glucose, and fructose as capping agents and Crataegus pentagyna leaf extract and NaBH4 as reducing agents. Vibrating‐sample magnetometer, field‐emission scanning electron microscopy, Fourier‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 43 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…16 On the other hand, the disaccharides, acting as capping agents, can regulate the morphology of the catalysts. [17][18][19] Since the disaccharides are carbohydrates with multiple hydroxyl groups in their molecular structure, they are able to provide a greater spatial site resistance in the formation of BiOCl. 20 As an example, Mohammadi-Aghdam et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 On the other hand, the disaccharides, acting as capping agents, can regulate the morphology of the catalysts. [17][18][19] Since the disaccharides are carbohydrates with multiple hydroxyl groups in their molecular structure, they are able to provide a greater spatial site resistance in the formation of BiOCl. 20 As an example, Mohammadi-Aghdam et al…”
Section: Introductionmentioning
confidence: 99%
“…16 On the other hand, the disaccharides, acting as capping agents, can regulate the morphology of the catalysts. 17–19 Since the disaccharides are carbohydrates with multiple hydroxyl groups in their molecular structure, they are able to provide a greater spatial site resistance in the formation of BiOCl. 20 As an example, Mohammadi-Aghdam et al synthesized Pr 3+ doped CaWO 4 nanostructures by sonication-assisted precipitation in the presence of a variety of capping agents such as glucose, maltose, fructose and lactose, and revealed that the photocatalytic activity of the nanostructures with maltose as the capping agent was considerably outperformed by other capping agents for dye degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysts are materials which a pair of electron-holes are created by arti cial light or sunlight on their surface so that the free radicals resulting from this action have the oxidizing properties of the material. In fact, photocatalysts only provide the conditions for reactions (16,17). nowday, the use of magnetic nanocatalysts in various elds of research has developed because nanocatalysts can be recycled (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…nowday, the use of magnetic nanocatalysts in various elds of research has developed because nanocatalysts can be recycled (18,19). Nanoparticles with a diameter between 1 and 100 nm have special properties such as regular morphology (17). Nanoparticles are very important because of their very small size and large ratio of surface to volume, which cause to physical and chemical differences in their properties (20).…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Some of applied strategies for remediation of organic pollutants in wastewater are coagulation, reverse osmosis, ion exchange, sedimentation, filtration, adsorption, chemical oxidation, biodegradation, photodegradation, and ozonation methods. [ 4–8 ] Usage of chemical treatment, especially advanced oxidation processes (AOPs) has been considered for effective removal of the bio‐refractory compounds. AOPs process produces hydroxyl radical to non‐selectively degradation of organic pollutants.…”
Section: Introductionmentioning
confidence: 99%